2020
DOI: 10.1016/j.vas.2020.100144
|View full text |Cite
|
Sign up to set email alerts
|

Detection and modeling of anti-Leptospira IgG prevalence in cats from Lisbon area and its correlation to retroviral infections, lifestyle, clinical and hematologic changes

Abstract: Highlights Anti- Leptospira IgG seroprevalence was estimated on cats from Lisbon, Portugal via ELISA. A mathematical model was applied to raw data to establish the real cut-off value of seroprevalence. Of the 243 samples, 59.3% tested positive for anti- Leptospira IgG. A positive correlation between low anti- Leptospira IgG and FIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In addition, a high cutoff for the data might not define seropositivity per se , but rather a high antibody response whose detection could be the primary objective of the analysis ( 30 , 31 ). The use of a high cutoff is also in accordance with a modeling approach where seropositivity might be subdivided into different levels ( 60 62 ). Therefore, our sensitivity-like approach seems to have the capacity to detect further serological associations beyond the ones based on the classical seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a high cutoff for the data might not define seropositivity per se , but rather a high antibody response whose detection could be the primary objective of the analysis ( 30 , 31 ). The use of a high cutoff is also in accordance with a modeling approach where seropositivity might be subdivided into different levels ( 60 62 ). Therefore, our sensitivity-like approach seems to have the capacity to detect further serological associations beyond the ones based on the classical seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of excretion of Leptospira among stray cats could be linked with exposition to higher doses or more frequent exposure due to their environment, contact with stray dogs and predation on small mammals. In addition, their immune system could be compromised and less efficiently control the bacteria carriage due to lower general health or co-infections, with feline immunodeficiency virus for example [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study also identified other risks related of leptospirosis to swine or cat raising. The previous studies indicated pigs and cats as reservoirs of Leptospira throughout the world and Vietnam [40][41][42][43][44]. Various serovars, such as Castellonis and Patoc, Tarassovi Mitis, Australis, Javanica, and Autumnalis in swine; and Javanica, Louisiana, Hebdomadis, and Castellonis in cats, were also found in Leptospira patients [21,[45][46][47].…”
Section: Discussionmentioning
confidence: 99%